Revitalisasi Nilai-Nilai Budaya: Memperkuat Jati Diri dan Ketahanan Budaya Lokal Melalui e-book Sejarah Untuk Siswa Sekolah Menengah Atas di Kabupaten Ciamis - Ratih, Dewi; Sondarika, Wulan; Suryana, Aan; Ramdani, Dadan; Melindawati, Melin (Jurnal Ketahanan Nasional, 2025)
ABSTRACTThis research explores the revitalization of cultural values and national identity building through the development of a history e-book aimed at high school students in Ciamis Regency, Indonesia. The research aims to assess how digital resources can enhance local cultural resilience and foster a sense of belonging among youth.Using Participatory Rural Appraisal (PRA) and Participatory Learning and Action (PLA) approaches as methodological frameworks, the research involved active participation from teachers in training, mentoring, practical application, and evaluation to assess the effectiveness of these digital resources in promoting cultural awareness and resilience as well as involving students in the process of developing teaching materials.The findings highlight the important role of participatory methods in engaging students and educators, leading to a deeper appreciation of local heritage and improved cultural identity. The results show that integrating local history into educational materials has a positive impact on students' understanding and appreciation of their cultural heritage, leading to increased engagement with local traditions and values. The resulting history e-book not only improves students' historical knowledge but also strengthens local cultural identity and resilience. This research concludes that the integration of cultural values in education can contribute to the development of local identity and resilience.